Amyloid precursor protein in aged nonhuman primates. - Martin, L J (1991)
In individuals with Alzheimer disease and in aged nonhuman primates, deposits of amyloid occur in senile plaques in brain parenchyma and in the walls of some meningeal and cortical vessels. Amyloid is primarily composed of beta/A4, a 4-kDa peptide derived from the transmembrane form of an amyloid precursor protein (APP). We examined the distribution of beta/A4 and APP (outside the beta/A4 domain) in cerebral cortices of monkeys ranging in age from 4 to 41 years. In all animals, APP immunoreactivity was present in cell bodies, proximal dendrites, and axons of cortical neurons. In aged animals, all of which showed senile plaques, large APP-positive axons were conspicuous, and APP immunoreactivity was present in neurites around beta/A4-immunoreactive plaques. In some plaques, APP-immunoreactive elements were located in proximity to deposits of beta/A4. The presence of APP immunoreactivity in neuronal perikarya, dendrites, axons, and in neurites within beta/A4-containing plaques supports the hypothesis that neurons can serve as one source of amyloid deposited in brain parenchyma.